2011
DOI: 10.1080/10401334.2011.536756
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of Team-Based Versus Small-Group Learning for Second-Year Medical Students: Does the Size of the Small Group Make a Difference?

Abstract: Team-based learning does not adversely affect examination performance. However, student satisfaction may be inferior, especially if compared to instruction in very small groups of 10 or fewer students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 7 publications
1
28
0
1
Order By: Relevance
“…Three hundred and thirty studies were identified, and 14 were included ( 2011; Willett et al 2011), two prospective cohort studies (Torralba et al 2009;Wiener et al 2009), one retrospective cohort study (Koles et al 2010), one concurrent cohort study (Zingone et al 2010) and seven non-concurrent cohorts (Nieder et al 2005;Levine et al 2004;Letassy et al 2008;Pileggi & O'Neill 2008;Mennenga 2010;Simaan et al 2010;Zgheib et al 2010). Of the 14 included studies, 12 took place in the United States, 1 in Lebanon (Zgheib et al 2010) and 1 in Austria (Wiener et al 2009).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three hundred and thirty studies were identified, and 14 were included ( 2011; Willett et al 2011), two prospective cohort studies (Torralba et al 2009;Wiener et al 2009), one retrospective cohort study (Koles et al 2010), one concurrent cohort study (Zingone et al 2010) and seven non-concurrent cohorts (Nieder et al 2005;Levine et al 2004;Letassy et al 2008;Pileggi & O'Neill 2008;Mennenga 2010;Simaan et al 2010;Zgheib et al 2010). Of the 14 included studies, 12 took place in the United States, 1 in Lebanon (Zgheib et al 2010) and 1 in Austria (Wiener et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The only study that did not include undergraduate learners assessed internal medicine residents in their first, second and third postgraduate years (Torralba et al 2009). All 14 studies assessed knowledge as a learning outcome, and 7 studies also assessed learner reaction (Koles et al 2005;Levine et al 2004;Letassy et al 2008;Conway et al 2010;Zingone et al 2010;Thomas & Bowen 2011;Willett et al 2011). None of the studies evaluated Kirkpatrick outcomes such as skills or improvements for patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations